The potential usage of thyroid hormones as sport doping - a mini-review - Gałązka, Jakub (Quality in Sport, 2022)
A thyroid gland is one of the most important organs of a human body. Thyroid hormones, at least in physiological concentration, have anabolic features. The aid of this review is to summarize knowledge on potential usage of thyroid hormones in sport doping. Thyroid hormones play a crucial role in skeletal muscles physiology. The exposition to T3 and T4 may improve myogenesis, muscles regeneration and muscles blood blow. In a long-time perspective, those hormones may help in reducing body weight. According to those mechanisms, thyroid hormones may be considered as a plausible agent in sport doping. However WADA guidelines does not include T3 or T4 in a list o sport doping substances, the debate on their inclusion is on-going, and the physicians should be aware of thyroid hormones effects on human metabolism from sports medicine perspective.